Drained instability analysis of sand under biaxial loading using a 3D material model. (October 2016) - Mukherjee, Mousumi; Gupta, Anurag; Prashant, Amit
Abstract: The diffused and localized instabilities in sand under drained biaxial loading have been analyzed here following a plane strain bifurcation framework, where the rate independent material is defined using a generalized 3D non-associative constitutive model. This study is focused on how various instability modes emerge with respect to initial density, confining pressure, and the applied boundary conditions. Results from large deformation framework have been compared with those from small deformation approximation and the later is noticed to fail in capturing the emergence of diffused modes and predicts delayed onset of localization. The theoretical predictions compares well with existing experimental observations.